2012
DOI: 10.1038/bmt.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant 18F-fluorodeoxyglucose positron emission tomography-based survival model in patients with aggressive lymphoma undergoing high-dose chemotherapy and autologous SCT

Abstract: 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) documented response after salvage chemotherapy has been reported to impact survival in patients with aggressive non-Hodgkin's lymphoma, especially diffuse large B cell lymphoma (DLBCL) undergoing high dose chemotherapy and autologous SCT (HDC auto-SCT). We reviewed the impact of 19 different prognostic/ predictive factors before salvage chemotherapy and post-salvage chemotherapy FDG-PET results in patients with aggressive lymphoma and developed an F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…This study reported a sensitivity of 8.3% and a specificity of 30.5% for pretransplant FDG-PET in predicting death in patients with newly diagnosed aggressive non-Hodgkin lymphoma (22). Three studies (17,20,26) reported sufficient data for the calculation of sensitivity and specificity of pretransplant FDG-PET in predicting treatment failure after ASCT in patients with refractory/relapsed aggressive non-Hodgkin lymphoma, which ranged between 58.8% and 73.3% and between 68.4% and 75.0%, respectively. There was no threshold effect (Spearman q = À1.000, P = 0.000) and no interstudy heterogeneity (I 2 = 0.0%).…”
Section: Subgroup Analysesmentioning
confidence: 81%
See 1 more Smart Citation
“…This study reported a sensitivity of 8.3% and a specificity of 30.5% for pretransplant FDG-PET in predicting death in patients with newly diagnosed aggressive non-Hodgkin lymphoma (22). Three studies (17,20,26) reported sufficient data for the calculation of sensitivity and specificity of pretransplant FDG-PET in predicting treatment failure after ASCT in patients with refractory/relapsed aggressive non-Hodgkin lymphoma, which ranged between 58.8% and 73.3% and between 68.4% and 75.0%, respectively. There was no threshold effect (Spearman q = À1.000, P = 0.000) and no interstudy heterogeneity (I 2 = 0.0%).…”
Section: Subgroup Analysesmentioning
confidence: 81%
“…Table 5 displays the results of the 11 included studies. Seven studies (17,18,20,(22)(23)(24)26) reported sufficient data for the calculation of sensitivity and specificity of pretransplant FDG-PET in predicting treatment failure after ASCT in all aggressive lymphomas (whether newly diagnosed aggressive, transformed indolent, or refractory/relapsed aggressive non-Hodgkin lymphoma), which ranged Four studies (18,20,22,26) reported sufficient data for the calculation of sensitivity and specificity of pretransplant FDG-PET in predicting death after ASCT in all aggressive lymphomas (whether newly diagnosed aggressive, transformed indolent, or refractory/relapsed aggressive non-Hodgkin lymphoma), which ranged between 8.3% and 87.5% and between 65.6% and 72.0%, respectively. There was no threshold effect (Spearman q = 0.000, P = 1.000), but there was interstudy heterogeneity (I 2 = 68.1%).…”
Section: Literature Searchmentioning
confidence: 99%
“…Details of methodology and design are fully explained in our previous report. 17 This study evaluates the impact of post salvage chemotherapy or pre-HDC ASCT FDG-PET among other prognostic or predictive factors at the time of relapse or progression before the initiation of salvage chemotherapy on post HDC ASCT persistent disease, progression, relapse or death in patients who underwent HDC ASCT. We also constructed a score-based predictive model based on pre-transplant FDG-PET results and other prognostic factors for post HDC ASCT residual/progressive disease (PD), relapse and death due to disease in these patients.…”
Section: Methodsmentioning
confidence: 99%
“…[114][115][116][117] In a recent retrospective study of 55 patients with relapsed/refractory DLBCL who were treated with HDC and autologous stem cell transplant (ASCT), 19 prognostic factors were analyzed in an integrative model to predict the outcome of the treatment. 118 Only PET positivity before the ASCT and HDC was predictive of disease-specific events (hazards ratio [HR]: 3.9, P 5 .01) and deaths (HR: 3.4, P 5 .04) in multivariate analyses. 118 A similar study in 141 patients with refractory HL analyzed 21 prognostic factors and showed IPS 3 or more (HR: 3.7, P 5 .001) and positive pre-ASCT PET (HR: 3.4; P 5 .011) to be associated with higher hazard for disease-specific death.…”
Section: Stem Cell Transplantation In Aggressive Lymphomamentioning
confidence: 97%
“…118 Only PET positivity before the ASCT and HDC was predictive of disease-specific events (hazards ratio [HR]: 3.9, P 5 .01) and deaths (HR: 3.4, P 5 .04) in multivariate analyses. 118 A similar study in 141 patients with refractory HL analyzed 21 prognostic factors and showed IPS 3 or more (HR: 3.7, P 5 .001) and positive pre-ASCT PET (HR: 3.4; P 5 .011) to be associated with higher hazard for disease-specific death. 119 In another study of patients with refractory HL, FDG-PET/CT allowed identification of high-risk patients who would benefit from tandem ASCT.…”
Section: Stem Cell Transplantation In Aggressive Lymphomamentioning
confidence: 97%